2011
DOI: 10.1016/j.phytochem.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic changes and molecular effects associated with Cr(III) and Cr(VI) treatments on germinating kiwifruit pollen

Abstract: The present study is aimed at identifying molecular changes elicited by Cr(III) and Cr(VI) on germinating kiwifruit pollen. To address this question, comparative proteomic and DNA laddering analyses were performed. While no genotoxic effect was detected, a number of proteins whose accumulation levels were altered by treatments were identified. In particular, the upregulation of some proteins involved in the scavenging response, cell redox homeostasis and lipid synthesis could be interpreted as an oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Increased malate levels in plants reinforce plant acid resistance and aluminum toxicity tolerance (Tesfaye et al 2001). Malate dehydrogenases were up-regulated under propamocarb treatment which is consistent with its expression pattern in rice and kiwifruit under abiotic stresses (Dooki et al 2006;Vannini et al 2011). Thus, the findings presented herein suggest that the accumulation of four proteins involved in defenses against stress following propamocarb treatment could be interpreted as a resistant response to propamocarb residue.…”
Section: Defense Against Stressessupporting
confidence: 81%
“…Increased malate levels in plants reinforce plant acid resistance and aluminum toxicity tolerance (Tesfaye et al 2001). Malate dehydrogenases were up-regulated under propamocarb treatment which is consistent with its expression pattern in rice and kiwifruit under abiotic stresses (Dooki et al 2006;Vannini et al 2011). Thus, the findings presented herein suggest that the accumulation of four proteins involved in defenses against stress following propamocarb treatment could be interpreted as a resistant response to propamocarb residue.…”
Section: Defense Against Stressessupporting
confidence: 81%
“…Moreover, Wang [79] in a survey to assess the genotoxic effects of Cr in water extracted from contaminated soil found that it was able to induce micronuclei in Vicia faba roots. Furthermore, Vannini and coworkers [80] evaluated the molecular changes induced by Cr(III) and Cr(VI) on germination kiwifruit pollen and concluded that neither Cr species induced a genotoxic effects. Both Cr species induced a strong reduction of proteins involved in mitochondrial oxidative phosphorylation and a decline in ATP levels [80].…”
Section: Genotoxicity Zou and Coworkersmentioning
confidence: 99%
“…Furthermore, Vannini and coworkers [80] evaluated the molecular changes induced by Cr(III) and Cr(VI) on germination kiwifruit pollen and concluded that neither Cr species induced a genotoxic effects. Both Cr species induced a strong reduction of proteins involved in mitochondrial oxidative phosphorylation and a decline in ATP levels [80].…”
Section: Genotoxicity Zou and Coworkersmentioning
confidence: 99%
“…However, the fern spore germination happens in the medium, therefore, it is somewhat more complex and affected by various environmental factors, such as light, gravity, calcium, phytohormone, and temperature (6). The protein functional skew in fern spores and pollen grains revealed from this study and recent proteomics studies on germinating pollen from kiwifruit (Actinidia deliciosa) (71,72), Nicotiana tabacum (73), rice (Oryza sativa) (26), Brassica napus (74), Pinus strobus (75), Picea meyeri (76,77), Picea wilsonii (78) and Arabidopsis (79,80) presented new evidence for the differentiation of fern spores and spermatophyte pollen (Fig. 10).…”
Section: Heterotrophic and Autotrophic Metabolisms Are Active Inmentioning
confidence: 63%
“…No photosynthetic proteins were found in pollen. This highlights that the remodeling of pollen tube cell wall, the loosening and hydrolyzing stigma surface cell and transmitting track of pistil, The data of germinating pollen were summarized and reclassified based on pollen proteomic studies on Oryza sativa (26), Actinidia deliciosa (71,72), Nicotiana tabacum (73), Brassica napus (74), Pinus strobus (75), Picea meyeri (76,77), Picea wilsonii (78), and Arabidopsis thaliana (79,80). The y axis represents the reclassified functional categories, and the x axis shows the percentage of identified proteins.…”
Section: Heterotrophic and Autotrophic Metabolisms Are Active Inmentioning
confidence: 99%